Hidup Dengan Leukemia: Studi Fenomenologi Remaja Penderita Leukemia - Adelia Eka Suryani; Muhammad Syafiq (Jurnal Psikologi Teori dan Terapan, 2016)
Leukemia becomes one of the most deadly disease for children and teenagers. This study was aimed to reveal the experience of teenagers suffering leukemia. Five teenagers suffering leukemia were purposively recruited for this study. Phenomenological approach.was used. Data collected using semi-structured interviews and analyzed using interpretative phenomenological analysis. The result reveals three major themes. The first theme is the first experience of being diagnosed as a leukemia sufferer. It explains how participants respond to medical diagnoses as leukemia sufferer. The second theme is the psychological effects of leukemia, and the third theme is the strategies used by participants to cope with problems imposed by leukemia they suffered. While all participants were rather similar in responding the leukemia diagnosis such as denial, sadness, and fear, they experienced different effects of their illness psychologically. Most participants perceived the effects of their illness negatively; however, there are some participants eventually get the positive meanings of their illness. All participants employ intrapersonal and interpersonal strategies in dealing with the difficulties caused by their illness and its effects.Key words: life experience, teenager, leukemiaAbstrak: Leukemia merupakan salah satu jenis penyakit kanker yang sering diidap anak dan remaja. Penelitian ini berusaha mengungkap pengalaman hidup remaja penderita leukemia. Pendekatan pada penelitian ini menggunakan kualitatif fenomenologis dengan analisis fenomenologis interpretatif. Partisipan dalam penelitian ini berjumlah lima orang yang diperoleh dari teknik purposif sampling. Data dikumpulkan menggunakan wawancara semi terstruktur. Hasil penelitian ini berhasil mengungkap tiga tema utama. Tema pertama ialah pengalaman awal mengetahui dan divonis leukemia. Tema kedua ialah dampak psikologis yang ditimbulkan dari leukemia. Tema terakhir ialah strategi untuk bertahan dan menghadapi leukemia. Hampir seluruh partisipan merespon diagnosis penyakit mereka dalam cara serupa yaitu terdiam sedih, menyangkal, dan rasa takut. Namun ada perbedaan dalam mengalami efek leukemia yang mereka derita. Umumnya mayoritas partisipan memaknai akibat penyakitnya dalam cara yang negatif, namun beberapa partisipan pada akhirnya dapat memperoleh makna yang lebih positif dari penyakit yang mereka derita. Namun demikian, semua partisipan menunjukkan kecenderungan untuk menangani secara aktif kesulitan yang diakibatkan oleh leukemia yang mereka derita dengan menggunakan strategi intrapersonal maupun interpersonal.